Family-Centered Interventions and Quality of Life of Clients with Ostomy - Arash Golpazir-Sorkheh; Teimor Ghaderi; Saeed Mahmoudi; Khalil Moradi; Amir Jalali (Hindawi Limited, 2022)
Background. Family-centered intervention can be used as a therapeutic intervention to improve the quality of life (QOL) in clients with ostomy. This study aimed to determine the effects of family-centered intervention on the QOL in ostomy clients. Methods. A quasi-experimental study was carried out with participation of 70 clients with colostomy and 70 caregivers (family members). The participants were selected through convenient sampling and randomly allocated into the experimental and control groups. The experimental group received family-centered education. The education program included four sessions, 50-60 min each, that were implemented in two weeks at hospital wards or clients' houses for the clients' companions. Afterwards, the caregivers implemented the care at home for one month. The subjects in the control group received routine care before being discharged. The QOL of the clients in both groups was measured using the city of hope-QOL-ostomy questionnaire before and one month after the intervention. Results. The mean scores of the QOL after family-centered intervention in the experimental and control groups increased from 197.97 to 207.49 and from 195.2 to 199.03, respectively. The paired t-test showed a significant change in the experimental and control groups after the intervention at a confidence level of 95% (p=0.0001; p=0.002). In addition, after the intervention, however, there was a significant difference between the two groups in all these areas except for social aspects (p=0.007). Conclusion. Family-centered intervention can be used as a therapeutic intervention to improve the QOL in clients with ostomy. The intervention was effective in the physical, spiritual, psychological, and social health of these clients.